The Image Of Lifestyle Change Through American Commercialism: A Study About Three Huge American Franchised Fast Food Restaurants - Setya Putri Rahayu (International Journal of Health Science and Technology, 2020)
Human diet pattern changes year by year, from the Paleolithic diet done by the ancient human to the diet pattern of modern society. Hence, it changes from food gathering diet to the diet that mostly consist of high carbohydrates, high fat, high sodium, high sugar, and low fiber. The impact of diet change triggers the increase uncommunicable diseases such as hypertension, diabetes, and heart attack due to imbalance metabolism of the body. Health impact due to lifestyle changes cannot be separated from American commercialism as the center of western diet pattern of the most people nowadays. The objective of this study was to investigate the image of lifestyle change through American commercialism upon three huge fast food franchised restaurants namely Mc Donald’s, KFC, and Pizza Hut. The research applied qualitative study with library research method to compare and contrast the information obtained from the reading process. The objects of the study were any information resources (books, journals, and websites) containing info about Mc Donald’s, KFC, and Pizza Hut. Those huge franchise restaurants were chosen since their influence has massively spread around the world. The result of the study showed that life style changes upon people around the world cannot be separated from the impact of American commercialism of those three huge franchised restaurants.